The Role of the Resistance Union of Lithuania in the Issue of Freedom for Lithuania - Dapkutė, Daiva (Genocidas ir rezistencija, 2000)
Disagreements between Lithuanian liberals and Catholics abroad resulted in the appearance of The Resistance Union of Lithuania, a liberal, political and cultural organisation. The RUL was founded in England in 1950, and rallied round two notable liberals – Stasys Žymantas and the chief of Lithuanian diplomacy, Stasys Lozoraitis. The main objective of the organisation was to, in every possible way, maintain and support the resistance movement and liberation of Lithuania. The RUL recognised the Lithuanian Diplomatic Corps, led by Lozoraitis, a legitimate state organ as authorised to represent Lithuania’s interests abroad. The organisation maintained secret contacts with the armed resistance in Lithuania (through Jonas Deksnys, recruited by the MGB), and intelligence services of different countries. Its relations with the VLIK (Chief Committee for the Liberation of Lithuania), claiming to represent Lithuania’s Government and resistance movement abroad, were strained. In fact the activities of the Resistance Union of Lithuania were rather limited. Its energy was concentrated on the support of the resistance movement in Lithuania and the conflict with the VLIK. Having no clear plans and being unable to meet new political situations, the organisation died.